In Search of a Monetary Anchor : A "New" Monetary Standard. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper explores recent versions of older ideas for stabilizing the value of money based on an independently defined unit of account. The gold standard was such a system, but suffered from gold's fluctuating relative value and the costly need to redeem money for gold. This paper explores monetary standards with relatively constant real values in which the supply of money is market determined by its redeemability for assets equal in value to its valuation basket (rather than for the basket itself). An SDR valuation basket with a constant real value might be widely adopted as a monetary standard.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet